Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Find the first 5 terms of the expansion in a power series $$y′=xe^{x}+2y^{2}$$

I've got a riccati equation $$ x e^{x}+2y^{2}, y(0)=0$$ After solving: $$y=e^{x}(x-1)+\frac{2}{3}y^{3} - 1$$

And I don't know how to go forward. Please help me.

share|improve this question
    
Your "After solving" is not correct. Most terms are correct, but the integral of $y^2\; dx$ is not $ y^3/3$ –  Ross Millikan May 20 '13 at 19:04
    
hmm..I thought it correct, but y'=xe^x + 2y^2 can be solved without second summand, can't it? –  wsevendays May 20 '13 at 20:13
    
No, you are integrating everything with respect to $x$. Take the simpler $y'=y$, which is solved by $y=Ae^x$. Your technique would give us $y=\frac {y^2}2$ which is not at all the same. –  Ross Millikan May 20 '13 at 20:16
    
Maybe I didn't understand that, but with or without mistakes I've got a correct answer. Thanks for a correction, I'll be more attentive. –  wsevendays May 20 '13 at 20:21

1 Answer 1

up vote 3 down vote accepted

You assume that there exist $a_i$ such that $$y = a_0 +a_1x + a_2x^2 + \cdots.$$
From here it is very easy to calculate power series expansions for $y', xe^x,$ and $2y^2$. Then you equate like powers of $x$ on both sides of the equality to get a relation between the $a_i$, and get a sequence of fairly simple equations in the $a_i$. The initial condition $y(0)=0$ tells you immediately that $a_0 = 0$ and from there you can usually get the other coefficients. Once you have $a_0,\ldots a_4$, you have the answer to the question.


To take a much simpler example that gives an idea of the method, suppose the equation were $$y' = y + 1$$ with the initial condition $y(0) = 0$.

We start with:

$$\begin{array}{rlrrr} y &= &a_0 &+a_1x &+ a_2x^2 &+ \cdots \\ y+1 &=& 1+ a_0 &+a_1x &+ a_2x^2 &+ \cdots \\ y' &=& a_1 &+2a_2x &+ 3a_3x^2 &+ \cdots \end{array}$$

Then equating the last two we have $$a_1 + 2a_2x + 3a_3x^2 + \cdots = 1 + a_0 + a_1x + a_2x^2 + \cdots$$

and equating coefficients of like powers gives equations in the $a_i$: $$ \begin{align} a_1 & =& 1+a_0\\ 2a_2 & = &a_1 \\ 3a_3 & = & a_2\\ &\vdots& \end{align} $$

Now $y(0) = 0$ tells us immediately that $a_0 = 0$. And the equations above then give us $a_1 = 1, a_2 = \frac12, a_3 = \frac16,\ldots$. So the series for $y$ is $$y = x + \frac12x^2 + \frac16x^3 + \cdots$$

which is in fact the power series for $y=e^x-1$.

share|improve this answer
    
Thank you very much! You have completely solved my problem. –  wsevendays May 20 '13 at 18:56
1  
I am glad that I could help. –  MJD May 20 '13 at 19:00

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.